2007
DOI: 10.1002/ccd.21022
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde recanalization of chronically occluded coronary arteries: Illustration and description of the technique

Abstract: Chronic total occlusions remain one of the last frontiers in interventional cardiology, with far lower procedural success rates compared with other lesion subsets. The benefits of successful treatment include improvements in angina and survival. One method, which may improve technical success rates, is the use of a retrograde approach. We report three cases employing a retrograde approach and describe the technique in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…With the antegrade approach the proximal and distal fibrous caps act as barriers forcing the guidewire to enter the subintimal space (24). The proximal cap of CTO lesions is believed to be harder than the distal cap (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…With the antegrade approach the proximal and distal fibrous caps act as barriers forcing the guidewire to enter the subintimal space (24). The proximal cap of CTO lesions is believed to be harder than the distal cap (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The observed higher frequency (52%) of subintimal tracking in the proximal one‐third of the CTO segment along with the higher rate of false lumen tracking in the antegrade group (57.9%) could be explained by (i) the work of Kukreja et al who showed that in the antegrade approach, the proximal and distal fibrous caps act as barriers forcing the GW to enter the subintimal space and (ii) the fact that the proximal cap of CTO lesions is believed to be harder than the distal cap as a result of higher pressure gradient . This may in part explain the numerical increase of SS with antegrade approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the antegrade approach, there is often difficulty in crossing the lesion with the guidewire in the proximal entry and distal reentry. Currently, the reason for this is believed to be the proximal and distal fibrous caps acting as barriers and forcing the guidewire to enter the subintima [11].…”
Section: Discussionmentioning
confidence: 99%